Learning from Experience Volume III: Lessons from the United Kingdom's Astute Submarine Program - Schank, John F. (RAND Corporation, 2011)
This volume presents a set of lessons learned from the United Kingdom's Astute submarine program that could help inform future program managers. Designing and building a submarine requires careful management and oversight and a delegation of roles and responsibilities that recognizes which party-the shipbuilder or the government-is best positioned to manage risks.